2011
DOI: 10.1159/000330061
|View full text |Cite
|
Sign up to set email alerts
|

Reliable and Valid Assessment of Clinical Bronchoscopy Performance

Abstract: Background: There have been several attempts to systematically assess performance in bronchoscopy. Earlier validation studies have used bronchoscopy simulators, not real-life performance in patients. Objectives: The aim of this study was to explore the reliability and validity of an assessment tool aimed for the use in a clinical setting. Methods: Five junior residents, 5 senior residents and 9 consultants performed 3 bronchoscopies each. All 57 bronchoscopies were video-recorded and assessed blindly and indep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
44
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 60 publications
3
44
0
Order By: Relevance
“…The variance due to performance of different cases (test-retest reliability) was considerably larger; this was expected, as we used consecutive patients of differing difficulty. This finding underlines the importance of assessing multiple procedures to reach a reliable judgment regarding the competence of a trainee [13]. The decision study showed that several feasible combinations of the number of assessors and the number of procedures resulted in acceptable generalisability coefficients (figure 3).…”
Section: Validity Evidence For the Assessment Toolmentioning
confidence: 74%
See 1 more Smart Citation
“…The variance due to performance of different cases (test-retest reliability) was considerably larger; this was expected, as we used consecutive patients of differing difficulty. This finding underlines the importance of assessing multiple procedures to reach a reliable judgment regarding the competence of a trainee [13]. The decision study showed that several feasible combinations of the number of assessors and the number of procedures resulted in acceptable generalisability coefficients (figure 3).…”
Section: Validity Evidence For the Assessment Toolmentioning
confidence: 74%
“…The assessment tool was developed by a group consisting of two respiratory physicians, a thoracic surgeon, and a professor of medical education, all with considerable experience in performance, teaching, and validation of endoscopic ultrasound and other procedures [13][14][15]. The tool was designed according to the original format for "objective structured assessment of technical skills", in which each item is rated on a scale from 1 to 5, with descriptive anchors in the middle and at the ends, and re-coded into a score from 0 to 4 points [16].…”
Section: Development Of the Assessment Toolmentioning
confidence: 99%
“…The WABIP Bronchoscopy Education Project [25] implemented in 2010 has successfully expanded a multidimensional educational program that includes assessment tools, training videos, a BronchAtlas video series, a collection of Fundamentals of Bronchoscopy PowerPoint lectures, patient-centered practical approach exercises, and The Essential Bronchoscopist series of books and training manuals 8 developed by Bronchoscopy International. Courses and faculty development programs have been held all over the world with the assistance of certified 8 Bronchoscopy Education Project by Bronchoscopy International is licensed under a Creative Commons Attribution-NoncommercialShare Alike 3.0 United States License.…”
Section: New Developments In Education Simulation and Computer Gamingmentioning
confidence: 99%
“…Courses and faculty development programs have been held all over the world with the assistance of certified 8 Bronchoscopy Education Project by Bronchoscopy International is licensed under a Creative Commons Attribution-NoncommercialShare Alike 3.0 United States License. Fig.…”
Section: New Developments In Education Simulation and Computer Gamingmentioning
confidence: 99%
“…Our group has developed and validated two assessment tools for assessing competence in bronchoscopy [20,21]. The first tool is designed to be administered on a virtual-reality bronchoscopy simulator and the second to be used in a clinical setting.…”
Section: Introductionmentioning
confidence: 99%